China’s Growing Involvement in Global Health Governance; Contributions and Implications - Qi, Huaigao (UIN Sunan Ampel Surabaya, 2021)
The outbreak of the COVID-19 global pandemic has exposed deficiencies in global health governance. China has been active in making intellectual and material contributions to the global fight against COVID-19 while achieving significant progress in containing the epidemic domestically. China’s contribution to global cooperation in the fight against the virus can be reflected in: (1) China has actively shared its experience in COVID-19 control and the treatment of infected cases with the international community; (2) China has sent 37 medical expert teams to help improve measures of diagnosis, treatment, prevention and control in 34 countries as of July 2021; (3) China has done its best to provide medical supplies to more than 150 countries and 13 international organizations as of July 2021; (4) China has made efforts to make vaccine accessible and affordable in developing countries. The implications of China’s involvement in global health governance include: (1) advocating the concept of “building a global community of health for all”; (2) supporting the leadership role of the World Health Organization in global health governance; (3) improving the global health governance system and WHO’s ability; and (4) cultivating public health talent with knowledge of international rules and diplomatic skills.